Equivalence of mother and father ratings of ADHD in children. Issue 2 (17th February 2018) - Mayfield, Abigail R.; Parke, Elyse M.; Barchard, Kimberly A.; Zenisek, RyAnna P.; Thaler, Nicholas S.; Etcoff, Lewis M.; Allen, Daniel N.
ABSTRACT: Obtaining data from multiple informants provides a more comprehensive diagnostic picture in the assessment of attention deficit hyperactivity disorder (ADHD). Differences in symptom ratings have been observed between parent- and teacher-report scales, though less information is available regarding differences between mothers and fathers. To address this gap, this study examines the rater agreement between mothers and fathers on the Diagnostic and Statistical Manual of Mental Disorders – Fourth Edition ( DSM-IV ) ADHD Symptom Rating Scale (DSM-ADHD-SRS). The participants consisted of 337 children diagnosed with ADHD who underwent comprehensive neuropsychological assessment. Confirmatory factor analysis indicates that a three-factor model comprising inattention, hyperactivity, and impulsivity symptoms provides the best fit for both mothers' and fathers' ratings. Mothers provided higher mean ratings for the inattention scale. These results suggest that the factor structure for the DSM-ADHD-SRS is the same, regardless of parent gender. However, symptoms of inattention may vary depending upon which parent completes the ratings. This discrepancy could lead to differences in diagnostic impressions in clinical evaluations.